Szwecja w polskiej recepcji powieści kryminalnych Henninga Mankella o komisarzu Wallanderze = Sweden in the Polish reception of Henning Mankell`s crime novels about Inspector Wallander - Chojnacki, Rafał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Henning Mankell was a writer compared to the great nineteenth-century realists. It is his crime novel series about Inspector Kurt Wallander that inspired Professor Przemysław Czapliński`s thesis that Scandinavian crime fiction tells us more about the postmodern society than mainstream fiction.
Keywords: powieść kryminalna; literatura szwedzka - tematyka - 20 w.; literatura szwedzka - tematyka - 21 w.; Mankell, Henning (1948-2015)